Regression test selection model: a comparison between ReTSE and pythia - Amir Ngah; Malcolm Munro; Zailani Abdullah; Masita A. Jalil; Mohamad Abdallah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
As software systems change and evolve over time regression tests have to be run to validate these changes. Regression testing is an expensive but essential activity in software maintenance. The purpose of this paper is to compare a new regression test selection model called ReTSE with Pythia. The ReTSE model uses decomposition slicing in order to identify the relevant regression tests. Decomposition slicing provides a technique that is capable of identifying the unchanged parts of a system. Pythia is a regression test selection technique based on textual differencing. Both techniques are compare using a Power program taken from Vokolos and Frankl’s paper. The analysis of this comparison has shown promising results in reducing the number of tests to be run after changes are introduced.